Local Governance and the Challenges of Economic Distress: The Case of Iligan City - Leilanie Q. Basilio; Jeremiah Cabasan (Philippine Institute for Development Studies (PIDS), 2004)
Trends in economic development influence population outcomes in an area. Increasing economic opportunities that are typically linked to industrialization enhance the attractiveness of a location and result to population increases. The inverse of this process could also be true, that is, an economic distress could hit an area and force its residents to leave and seek better forts. Iligan City experienced rapid urbanization for almost five decades due to industrialization. However, the City saw remarkable outward migration in the latter half of the 1990s. This out-migration phenomenon was strongly attributed to the economic difficulties which endured late last decade. The closure of the National Steel Corporation, Iligan Citys main employer and biggest taxpayer, in particular aggravated the economic condition of the City. This case study describes the economic challenges that altered population pattern and welfare of Iligan City. The paper also presents the interventions that the local government embarked on to minimize the impact of the economic crisis including policy changes and shifts in development strategies.
Keywords: 330; industrialization; Iligan City; de-urbanization; de-population; National Steel Corporation; Kommunalverwaltung; Bevölkerungsentwicklung; Stadtflucht; Industrialisierung; Insolvenz; Wirtschaftskrise; Wirtschaftsförderung; Wirtschaftsförderung; Philippinen